Role of Nitrogen Uptake and Grain Number on the Determination of Grain Nitrogen Content in Old Durum Wheat Cultivars - Francesco Giunta; Marina Mefleh; Giovanni Pruneddu; Rosella Motzo (Agronomy, 2020)
Old durum wheat cultivars are attracting renewed attention due to their suitability to low input agricultural systems. Fourteen old durum wheat cultivars were analyzed in two field trials to assess the effect of grain number and N absorbed and translocated by the crops on grain protein percentage. The mean grain yield was below 3 t ha−1 and strongly associated with the number of grains m−2 (GNO) (r = 0.97 ***). Grain yield displayed a low sensitivity to severe terminal stressful conditions due to the ability of the old durum wheat cultivars to maintain high grain weights despite the high temperatures and short time available for grain filling caused by their late anthesis. The N source for the growing grains was mainly dependent on pre-anthesis N uptake, which was positively associated with the total biomass produced by anthesis. The tall cultivars generally left a greater amount of N m−2 (8–15 g m−2) in their straw compared with shorter ones (5–6 g m−2). The low and variable GNO modulated the amount of N potentially available for each grain and probably limited the possibility of delivering the large N source to the grains. The large grains played a positive role in determining both grain yield (by compensating for the low GNO) and grain protein percentage, as their high grain filling rate was associated with a high N accumulation rate, and hence with a high grain N content and protein percentage.